LOW-LEVELS OF SELENIUM IN MOTHERS AND THEIR NEWBORNS IN PREGNANCIES WITH A NEURAL-TUBE DEFECT - GUVENC, H; KARATAS, F; GUVENC, M; KUNC, S; AYGUN, AD; BEKTAS, S (Amer Acad Pediatrics, 1995)
Objective. Very few data are presented in the literature about selenium. (Se) in human fetal development. The aim of this paper was to study the relationship between maternal and neonatal Se status and neural tube defects (NTDs). Patients and methods. Serum and hair samples were obtained from 20 nonpregnant women, 32 healthy mothers with normal newborns, and 28 mothers who had a newborn with NTD, and their newborns at delivery. Serum Se levels, as ng/mL, and hair Se levels, as mu g/g, were determined on a Perkin-Elmer 1000 spectrophotometer (United Kingdom) by fluorometry. Results. The mean maternal serum and hair Se concentrations in the NTD group (42.9 +/- 1.75 ng/mL, 277 +/- 7.73 ng/g, respectively) were significantly lower than those of the control healthy mothers (50.2 +/- 2.35 ng/mL, 300 +/- 6.10 ng/g, respectively) and the nonpregnant women (58.1 +/- 3.12 ng/mL, 315 +/- 7.64 ng/g, respectively). A significant decrease in concentrations of Se in serum and hair was observed in newborns with a NTD (26.0 +/- 1.55 ng/mL, 181 +/- 3.71 ng/g, respectively) compared with healthy newborns (32.6 +/- 1.70 ng/mL, 204 +/- 4.43 ng/g, respectively). Conclusions. Maternal Se deficiency during pregnancy was thought to be one of the factors responsible for NTDs. However, the lowered serum and hair Se concentrations may be secondary manifestations of an abnormal pregnancy and did not contribute to its production. More studies on maternal Se status during the antenatal period, especially early gestation and neonatal Se status including normal newborns and NTD infants, are needed.
Keywords: MOTHER; NEWBORN; NEURAL TUBE DEFECT; SELENIUM